Korelasi antara interleukin-6 dengan responawal terapi eritropoietin pada pasien hemodialisis reguler - Vally Ramayanda; Dairion Gatot; Savita Handayani; Syafrizal Nasution (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introuction:In hemodialysis patients conditionsinflammation can play a main role in causing hiporesponsif erythropoietin therapy. Interleukin - 6 (IL-6) was a predictor of mortality that is more powerful than other inflammatory markers.To determine correlation between Interleukin-6 with respon Erythropoirtin Stimulating Agent (ESA) which assessed based on changes of hemoglobin level before and after ESA treatment to regular hemodialysis patients.Methods: The cohort study of experimental methods of measurement data pre and post test from December 2014 to Mei 2016with 50 hemodialysis patients do a complete blood count, interleukin - 6 and iron profiles before and 1 month after the intervention. Patients were given injections of Recombinant Human Erythropoietin(rHuEPO) for 1 month subcutaneously at a dose of 2,000-4,000 each time the hemodialysis procedure. Kolmogorov-Smirnov test was used to determine the distribution of the data. Spearman assess the association between interleukin - 6 with an increase hemoglobin before and after be given erythropoietin therapy.Results : The mean levels of IL - 6 was 20.24 pg/mL and the mean increase in hemoglobin after erythropoietin administration of 0.56 mg/dL. Found a significant negative correlation (r = -0.287 ; p = 0.043) between IL - 6 and increased hemoglobin level, the higher the levels of IL-6, then the increase of hemoglobin level after erythropoietin administration will be lower than expected. Conclusion : In our trial, we found a negative correlation between Interleukin-6 with hiporesponsifity erythropoietin in reguler hemodialysis patientsKeywords : erythropoietin, inflammation, IL-6, hemodialysis, hemoglobin